Minimally Invasive Cardiac Surgery versus Sternotomy - Pain Investigation - Silva,Juliana Fernandes (2020)
Abstract Background: Treatment of postoperative (PO) pain is essential after surgery, as it contributes to a faster rehabilitation. Assessment of PO pain after minimally invasive (MI) surgery has not been regularly addressed, especially when compared with median sternotomy (MS). Objective: This study aims to evaluate the intensity of thoracic pain in the PO period in patients subjected to MI surgery and MS. Methods: This study compared the intensity of thoracic pain in 34 patients subjected to minimally invasive (MI; n = 17) and median sternotomy (MS; n = 17) from June 2015 to June 2016. The intensity and sites of pain in the PO period, assessed using the visual numeric pain scale, and the need for pain medications were analyzed using the Student’s t-test and the z test, with confidence level of 95% (p < 0.05). Results: Almost all patients reported pain on the third PO day (MS = 94.1% and MI = 88.2%; p = 0.5410). On the seventh PO day, there were significantly more patients free of pain in the group of patients subjected to the MI procedure (MS = 94.1% and MI = 64.7%; p = 0.0341). also, these patients reported fewer pain sites (3rd PO day: MS = 3.2 ± 1.5; MI = 1.5 ± 1.2; p = 0.001; 7th PO day: MS = 3.1 ± 1.4; MI = 0.9 ± 0.9; p = 0.000). Patients undergoing MS reported higher pain intensity and longer lasting pain (3rd PO: MS = 4.8 ± 2.2; MI = 3.0 ± 1.6; 7th PO: MS = 5.3 ± 2.0; MI = 1.2 ± 1.3; p = 0.001), with no difference in pain intensity between the third and the seventh PO days (p = 0.4931). In addition, patients subjected to MI procedure had a significant decrease in pain intensity from the third to the seventh PO days (p = 0.001). Conclusion: According to these results, we concluded that a MI procedure leads to lower intensity of pain in the PO period (from the third PO day on) when compared to a MS; also, patients undergoing MI patients reported fewer pain sites.